Effects of ginseng on two main sex steroid hormone receptors: estrogen and androgen receptors - Joonwoo Park (Journal of Ginseng Research, 2017)
Ginseng has been used in China for at least two millennia and is now popular in over 35 countries. It is one of the world's popular herbs for complementary and alternative medicine and has been shown to have helpful effects on cognition and blood circulation, as well as anti-aging, anti-cancer, and anti-diabetic effects, among many others. The pharmacological activities of ginseng are dependent mainly on ginsenosides. Ginsenosides have a cholesterol-like four trans-ring steroid skeleton with a variety of sugar moieties. Nuclear receptors are one of the most important molecular targets of ginseng, and reports have shown that members of the nuclear receptor superfamily are regulated by a variety of ginsenosides. Here, we review the published literature on the effects of ginseng and its constituents on two main sex steroid hormone receptors: estrogen and androgen receptors. Furthermore, we discuss applications for sex steroid hormone receptor modulation and their therapeutic efficacy.